Retinal tears and rhegmatogenous retinal detachment after intravitreal injections: its prevalence and case reports - Karabag, Revan Yildirim; Parlak, Melih; Cetin, Gölgem; Yaman, Aylin; Saatci, Ali Osman (Digital Journal of Ophthalmology, 2015)
Purpose To report the prevalence of postoperative retinal tear or rhegmatogenous retinal detachment secondary to intravitreal injections. Methods Surgical and medical records of patients who received intravitreal injections at the practice of a single retina specialist from January 2004 to May 2013 and who were followed for at least 6 months were investigated retrospectively. Results During the study period, a total of 3,907 intravitreal injections were performed in 1,049 eyes of 784 patients (416 males [47%]). The mean number of injections per eye was 3.72 ± 3.43 (range,1-22). The mean age of the participants was 67.03 ± 13.56 (range, 5-94 years). The mean follow-up time was 31.98 ± 22.86 months (range, 6-144 months). Retinal break or rhegmatogenous retinal detachment occurred in 3 injections of 3 eyes, yielding an overall prevalence of 0.077% per injection and 0.29% per eye. Conclusions Retinal tear and rhegmatogenous detachment are rare complications of intravitreal injection. Precautions should be taken especially in patients having predisposing conditions, such as high myopia, or any other vitreoretinal disorders.